Motivasi kerja memoderasi pengaruh komitmen organisasi, gaya kepemimpinan dan ambiguitas peran terhadap kinerja auditor - Jailani Sidik; Devi Safitri (Penerbit Goodwood, 2020)
Purpose: This study is to investigate how work motivation moderates organizational commitment, leadership style, and role ambiguity in the performance of the auditor. Research Methodology: The subject of this investigation is the audit firm in Pekanbaru, Medan and Padang with the assumption that each audit firm has four accountants. The test equipment used Statistical Product and Service Solution (SPSS) ver. 23.0. Results: The results of hypothesis test show that organizational commitment, leadership style and role ambiguity influence the performance of the auditor. Then for a hypothesis that is moderated by work motivation, show that work motivation moderates the relationship between organizational commitment, leadership style, and role ambiguity influence the performance of the auditor. Limitations: Unreturned questionnaires, limited scope of research area, and limited variable became the limitations of this study. Contribution: In accordance with its responsibility to provide good audit results and reliability, the auditor must not only have competence but also relate to the involvement of the organizational commitment, leadership style, and role ambiguity that exists in the auditor. It is necessary to improve the performance of the auditor, thereby increasing the confidence of financial statement users about the result of financial statement audits based on applicable auditing standards. Keywords: Organizational commitment, Leadership style, Role ambiguity, Work motivation, Auditor performance